PENGARUH TINGGI MUKA AIR TANAH DAN PEMUPUKAN TERHADAP POPULASI DAN JENIS FUNGI PADA TANAH GAMBUT DENGAN SERASAH DAUN AKASIA (Acacia crassicarpa) - Tiara Athahirah; Wawan '; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Riau has the peatland appreciable to be used in the development of agriculture, plantation and development of Industrial Plantation Forest (HTI). One of the plants HTI is a widely developed Acacia crassicarpa. Function of Acacia crassicarpa are as raw material then produce organic matter. This study aims to determine the effect of water level and fertilization on populations and species of fungi in peatland with litter of acacia (Acacia crassicarpa). This research was conducted in the Screen House, Laboratory of Plant Agriculture Faculty, University of Riau and Plant Protection Unit Office of Food Crops and Horticulture Riau Province, from July to November 2013. The research was conducted experimentally using completely randomized design (CRD) non-factorial with 6 treatments and 3 replications. The data obtained were analyzed statistically using analysis of variance with Duncan's New Multiple Range Test (DNMRT) at 5% level. Parameters observed were total fungi and types of fungi (macroscopic and microscopic observations). The results showed that the water level without fertilization affect on total fungi tested. The highest of Total fungi achieved in the treatment of water level without fertilization 30 cm. Treatment of water level with or without fertilizer N, P, K does not affect the type of fungi that exist are Trichoderma sp and Mucor sp, except in water level of 60 cm with N, P, K is Penicillium sp. Based on the identification of characteristic morfologis found 3 Acacia crassicarpa types of fungi namely: Trichoderma sp, Mucor sp and Penicillium sp. Fungi were found in leaf litter Acacia crassicarpa dominated by Trichoderma sp and Mucor sp on all treatments water levels. Keywords : : water level, fertilization, litter of acacia and fungi